Assessing the potential of full-scale phosphorus recovery by struvite precipitation - Jaffer, Yasmin (Cranfield University, 2000)
Formation of struvite (MgNH4P04.6H20) at sewage treatment works can cause major operational problems and decrease efficiency. Struvite has a commercial value and the controlled formation of it, in a specified location, would be beneficial. A mass balance was conducted at full-scale across a whole sewage treatment plant, to identify a stream to conduct bench-scale struvite crystallisation studies on. The most suitable stream was identified as the centrifuge liquors. The average flow of the liquor stream was 393 m3 d'1 and the composition was as follows: 167 mg L'1 phosphorus, 44 mg L'1 magnesium, 615 mg L 1 ammonium, 56 mg L 1 calcium and 2580mg L'1 of alkalinity. The pH averaged at 7.6 and the stream had a predicted struvite precipitation potential of 140 mg L'1. Struvite crystallisation occurred quickly during the trials, by raising the pH of the centrifuge liquors to 9.0 and dosing with magnesium. Up to 97% phosphorus removal, as struvite was achieved. Struvite formation occurred when the molar ratio of magnesium : phosphorus was at least 1.05 : 1. Below this ratio phosphorus removals of 72% were observed, but not exclusively as struvite. Annual yields of struvite were calculated to be 42-100 tonnes a year, depending on the dose regime. Revenue from the sale of produced struvite could be £8,400-20,000 a year.